2015
DOI: 10.1007/s13580-015-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-characterized amplified polymorphism markers for selecting rind stripe pattern in watermelon (Citrullus lanatus L.)

Abstract: The inheritance of foreground stripe pattern in rind of watermelon fruits [Citrullus lanatus (Thunb.) Matsum. & Nakai] was evaluated and molecular markers for selecting the Jubilee-type (JT) stripe pattern were developed based on bulked segregant analysis (BSA). Divergence in rind pattern among F2 progeny derived from crossing Crimson-type (CT) 'Arka Manik' (AM) with JT 'TS34' (TS) indicated that stripe pattern is a quantitative trait controlled by more than one gene. The BSA of F2 plants (derived from a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…2). Thus, PCA in this study using SNPs detected in 19 inbred lines further confirmed that a striped rind pattern is one representative fruit trait that distinguishes the Crimson-type from the non-Crimson-type as previously noted (Kim et al, 2015a).…”
Section: Analysis Of Relationship Between the Inbred Lines By Snp Locsupporting
confidence: 87%
See 1 more Smart Citation
“…2). Thus, PCA in this study using SNPs detected in 19 inbred lines further confirmed that a striped rind pattern is one representative fruit trait that distinguishes the Crimson-type from the non-Crimson-type as previously noted (Kim et al, 2015a).…”
Section: Analysis Of Relationship Between the Inbred Lines By Snp Locsupporting
confidence: 87%
“…4. In our previous study (Kim et al, 2015a), a major QTL for fruit shape was detected from Chr. 3; however, no SNP hot spot was found for the fruit shape trait in this study.…”
Section: High Density-snp Regions Specific To Fruit-related Traitsmentioning
confidence: 98%
“…for 1 min; 35 cycles at 94°C for 15 s, 55°C for 30 s, and 72°C for 1 min; and ending at 72°C for 3 min. For fruit stripe pattern, a SCAR marker wsb6 -11 reported by Kim et al (2015b), was examined (Table 1). PCR amplification of the wsb6 -11 marker was performed using a touch -down PCR program, as described above.…”
Section: Marker Genotyping For Fruit -Related Traitsmentioning
confidence: 99%
“…This marker was developed by BSA of F2 progeny derived from AM [Crimson -type stripe pattern (CSP)] × TS [Jubilee -type stripe pattern (JSP)], and was reported to be effective in selecting the Jubilee -type stripe pattern (Kim et al, 2015b).…”
Section: Marker -Trait Associationmentioning
confidence: 99%
See 1 more Smart Citation